Effects of plant spacing on yields and nutritive values of hybrid Napier grass CO-3 in dry zone of Sri Lanka - Sinthika, K.; Sinniah, J.; Sivaneson, S.; Sarmini, N. (Ruhuna International Science and Technology Conference, 2014)
An experiment was conducted to study the effect of spacing (60cm X 60cm, 60cm X 90 cm) on yield, growth parameters viz. fourth leaf length, fourth leaf width, plant height, number of leaves per plant and number of tillers per plant and nutritive values viz. crude protein (CP), crude fiber (CF), neutral detergent fiber (NDF), acid detergent fiber (ADF), and ash content of CO-3 fodder grass during May-July 2013 at Regional Agricultural Research and Development Centre, Killinochchi, Sri Lanka. The experiment was conducted using complete randomized block design with four replicates. Fresh matter yield at 60 days after harvesting was not influenced by spacing. All growth parameters showed significant increase with two weeks interval up to 60 days. Crude protein (CP), crude fiber (CF), neutral detergent fiber (NDF), acid detergent fiber (ADF), and ash content were not significantly influenced by the plant spacing used in this experiment. Results concluded that spacing could be increased (60cm x 90cm) than recommended spacing (60cm x 60cm) without significantly affecting yield and nutrient composition of CO-3 in the dry zone of Sri Lanka
Keywords: CO-3; growth parameters; hybrid Napier; nutritive value; yield